Spinal aspergillosis: a rare clinical case and a review of the literature - Denis G. Naumov; Arkady A. Vishnevsky; Andrey A. Karpushin; Mikhail M. Shchelkunov; Sergey G. Tkach (Хирургия позвоночника, 2023)
Objective. To analyze long-term results of treatment of a patient with recurrent lumbar aspergillosis and to systematize the literature data. Material and Methods. Long-term follow-up results of treatment of recurrent Aspergillus spondylitis in a 48-year-old patient who underwent primary surgery for reconstruction of the anterior spinal column through the anterior approach were studied. Literature data on the treatment of spinal aspergillosis from 2000 to 2022 were systematized. Results. The key method for the etiological verification of spinal aspergillosis is percutaneous bone biopsy from the lesion, followed by histological and bacteriological examination of the material. Isolated anterior spinal column reconstruction through the anterior approach ensures the achievement of local control of the infection process, but a short course of antimycotic chemotherapy after surgery is a factor of disease recurrence. The optimal duration of antimycotic chemotherapy in the postoperative period is at least 3 months, with voricon- azole being the drug of choice. Conclusion. Spondylitis caused by Aspergillus spp. is a special form of inflammatory spine disease requiring obligatory percutaneous bone biopsy for etiological verification. A multidisciplinary therapeutic approach including a course of conservative antimycotic therapy for at least 3 months, surgical debridement and reconstruction of the affected spinal motion segments provide the best clinical results.